MODEL PROBLEM BASED LEARNING SECARA ONLINE UNTUK MENINGKATKAN HASIL BELAJAR KIMIA TENTANG ASAM AMINO DAN PROTEIN - SINI ALIYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to determine the effectiveness of the Problem Based Learning model with the online method in improving chemistry learning outcomes about carbon chemistry, especially amino acids and proteins in class XII MIPA 3 SMA Negeri 2 Bantul in the 2020/2021 academic year. In this study the data were taken from disciplinary observations (student attendance), student activity in question and answer, responsibility in collecting assignments and test results, this data was analyzed descriptively qualitatively. The results showed that in learning using the Problem Based Learning model with this online method, 94.12% of students achieved completeness, 95.5% of students were disciplined in attendance, 81.2% of students were active in questioning and 100% of students were responsible for completing their assignments. Discipline, activeness and responsibility is very helpful for students in mastering the subject matter so that they can get high learning outcomes. ABSTRAKPenelitian ini bertujuan untuk mengetahui efektifitas model Problem Based Learning dengan metode online dalam meningkatkan hasil belajar kimia tentang kimia karbon khususnya asam amino dan protein pada kelas XII MIPA 3 SMA Negeri 2 Bantul tahun pelajaran 2020/2021. Dalam penelitian ini data diambil dari observasi kedisiplinan (kehadiran siswa), keaktifan siswa dalam tanya jawab, tanggung jawab dalam pengumpulan tugas dan hasil tes, data ini dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa dalam pembelajaran menggunakan model Problem Based Learning dengan metode online ini 94,12% siswa mencapai ketuntasan, 95,5 % siswa disiplin dalam kehadiran, 81,2 % siswa aktif dalam tanya jawab dan 100 % siswa bertanggungjawab dalam menyelesaikan tugasnya. Kedisiplinan, keaktifan serta tanggungjawab ini sangat membantu siswa dalam menguasai materi pelajaran sehingga mereka bisa mendapatkan hasil belajar yang tinggi.